Low Cell-Matrix Adhesion Reveals Two Subtypes of Human Pluripotent Stem Cells - Leqian Yu; Junjun Li; Jiayin Hong; Yasuhiro Takashima; Nanae Fujimoto; Minako Nakajima; Akihisa Yamamoto; Xiaofeng Dong; Yujiao Dang; Yu Hou; Wei Yang; Itsunari Minami; et al. (Stem Cell Reports, 2018)
Summary: We show that a human pluripotent stem cell (hPSC) population cultured on a low-adhesion substrate developed two hPSC subtypes with different colony morphologies: flat and domed. Notably, the dome-like cells showed higher active proliferation capacity and increased several pluripotent genes’ expression compared with the flat monolayer cells. We further demonstrated that cell-matrix adhesion mediates the interaction between cell morphology and expression of KLF4 and KLF5 through a serum response factor (SRF)-based regulatory double loop. Our results provide a mechanistic view on the coupling among adhesion, stem cell morphology, and pluripotency, shedding light on the critical role of cell-matrix adhesion in the induction and maintenance of hPSC. : When culturing hPSCs on low-adhesion substrate (gelatin nanofiber), Dr. Liu Li and her colleagues found two subtypes with different colony morphologies. The dome-like cells showed higher proliferation capacity and KLF4/5 and NANOG expression than the monolayer cells. A serum response factor-based regulatory double loop was proposed to explain how cell-matrix adhesion mediates the interaction between cell morphology and pluripotency genes. Keywords: human pluripotent stem cells, cell-matrix adhesion, stem cell morphology, single-cell culture, heterogeneity, serum response factor, nanofiber, mathematical model